2012
DOI: 10.1093/jxb/ers340
|View full text |Cite
|
Sign up to set email alerts
|

Blue light is essential for high light acclimation and photoprotection in the diatom Phaeodactylum tricornutum

Abstract: The objective of the present study was to test the hypothesis that the acclimation to different light intensities in the diatom Phaeodactylum tricornutum is controlled by light quality perception mechanisms. Therefore, semi-continuous cultures of P. tricornutum were illuminated with equal amounts of photosynthetically absorbed radiation of blue (BL), white (WL), and red light (RL) and in combination of two intensities of irradiance, low (LL) and medium light (ML). Under LL conditions, growth rates and photosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 56 publications
12
97
4
Order By: Relevance
“…In a previous study we have shown that photoreceptors are involved in the processes of photoacclimation and photoprotection in diatoms [28]. Cultivation of P. tricornutum under low irradiance of BL induced the generation of a high light-adapted phenotype whereas a low light-adapted phenotype was observed for cultures grown under equivalent amounts of red light (RL).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we have shown that photoreceptors are involved in the processes of photoacclimation and photoprotection in diatoms [28]. Cultivation of P. tricornutum under low irradiance of BL induced the generation of a high light-adapted phenotype whereas a low light-adapted phenotype was observed for cultures grown under equivalent amounts of red light (RL).…”
Section: Introductionmentioning
confidence: 99%
“…We identified three aureochromes, which have been regarded as photoreceptors in P. tricornutum and T. pseudonana [39]. Under HL stress, no significant change was observed in relative abundance of aureochromes, suggesting that light signal transmission might be not regulated by change of expression abundance of aureochromes.…”
Section: Resultsmentioning
confidence: 99%
“…P. tricornutum UTEX 646 was grown as previously described in [15] in modified f/2 medium [46] with 16 g l −1 marine salt concentration and no silica. The cells were grown semi-continuously as airlift-cultures in a rectangular culture tank of 3 cm depth under illumination with either blue (465±10 nm) or red (660±10 nm) at light intensities of 24 and 40 µmol photons m −2 s −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that BL is involved in the light acclimation of Phaeodactylum tricornutum [15]. They demonstrated that a typical HL phenotype with a reduced Chl a content per cell and a high photosynthetic capacity can be generated only in the presence of BL.…”
Section: Introductionmentioning
confidence: 99%